2008
DOI: 10.1038/labinvest.3700720
|View full text |Cite
|
Sign up to set email alerts
|

SHP-1 deficiency and increased inflammatory gene expression in PBMCs of multiple sclerosis patients

Abstract: Recent studies in mice have demonstrated that the protein tyrosine phosphatase SHP-1 is a crucial negative regulator of cytokine signaling, inflammatory gene expression, and demyelination in central nervous system. The present study investigates a possible similar role for SHP-1 in the human disease multiple sclerosis (MS). The levels of SHP-1 protein and mRNA in PBMCs of MS patients were significantly lower compared to normal subjects. Moreover, promoter II transcripts, expressed from one of two known promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 88 publications
4
77
0
Order By: Relevance
“…The amount of SHP-1 levels may also be important for mediating autoimmune disease as Deng et al (43) reported enhanced EAE disease severity, more frequent relapses, and decreased survival following immunization of B10.PL me-v mice with myelin basic protein Ac 1-11. A further role for SHP-1 in the autoimmune T cell response is supported by the recent report detailing decreased SHP-1 gene activity in PBMC's of MS patients (44). Together, our results and the published findings highlight SHP-1 as an important point of control for autoimmune T cell responses.…”
Section: Discussionsupporting
confidence: 79%
“…The amount of SHP-1 levels may also be important for mediating autoimmune disease as Deng et al (43) reported enhanced EAE disease severity, more frequent relapses, and decreased survival following immunization of B10.PL me-v mice with myelin basic protein Ac 1-11. A further role for SHP-1 in the autoimmune T cell response is supported by the recent report detailing decreased SHP-1 gene activity in PBMC's of MS patients (44). Together, our results and the published findings highlight SHP-1 as an important point of control for autoimmune T cell responses.…”
Section: Discussionsupporting
confidence: 79%
“…Taken together, the findings of these studies indicate that SHP-1 is a key regulator of inflammation in the CNS that may be relevant to the pathogenesis of MS. Indeed, we have recently reported that SHP-1 expression and function are deficient in the leukocytes of MS patients compared to those in the leukocytes of normal human subjects (21).…”
mentioning
confidence: 99%
“…For instance, macrophages have been identified as the major responders to CNS chemokines and producers of a number of proinflammatory cytokines, chemokines, and toxic molecules known to promote demyelination (32,44,63,85,90,91,93,103). Interestingly, both the brains of MS patients and the brains of experimental animals with MS-like diseases contain activated transcription factors like NF-B (34, 40), STAT1 (35,37,40), and STAT6 (18,21,109), which can lead to enhanced expression of these inflammatory molecules. Based on the findings of our previous work, we propose that the modulation of inflammatory signaling via these transcriptional pathways may be deficient in the leukocytes, including the macrophages, of MS patients and that this deficiency is responsible for susceptibility to inflammatory demyelinating processes within the CNS.…”
mentioning
confidence: 99%
“…SHP-1 mRNA and protein expression and that MS patients have elevated levels of inflammatory gene expression controlled by SHP-1 (Christophi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of SHP-1 in the CNS as seen in motheaten (me/ me) mice leads to myelin pathology (Massa et al 2000(Massa et al , 2004 that may be caused by effects of an increased inflammatory milieu and/or specific alterations in cytokine signaling on the myelin-forming oligodendrocytes. Importantly, it was recently shown that leukocytes of MS patients have decreased levels of the phosphatase SHP-1, which results in increased inflammatory gene expression (Christophi et al 2008). Furthermore, SHP-1 plays a critical role in fighting CNS viral infections such as Theiler's murine encephalomyelitis virus (TMEV) (Massa et al 2002).…”
mentioning
confidence: 99%